СОЦІАЛЬНО-ПСИХОЛОГІЧНИЙ ТРЕНІНГ ЯК МЕТОД РОЗВИТКУ КОМУНІКАТИВНОЇ КОМПЕТЕНТНОСТІ ДЕРЖАВНИХ СЛУЖБОВЦІВ - Соловей, Оксана Анатоліївна; Solovei, Oksana (My University, 2013)
У статті розглядається комунікативна компетентність як складова життєвого і професійного успіху фахівця державної служби. Розглянуто підходи до визначення поняття комунікативної компетентності, розглянуто характеристики, що впливають на ефективну комунікацію. Здійснено аналіз особливостей впровадження соціально-психологічного тренінгу як активного методу розвитку комунікативної компетентності. The article deals with the communicative competence as a part of life and professional success of a public service specialist. The approaches to the definition of the communicative competence and characteristics that influence the effective communication are examined. The analysis of peculiarities of social and psychological training introduction as an active method of communicative competence development is realized.
SOCIAL AND PSYCHOLOGICAL TRAINING AS A METHOD OF DEVELOPMENT OF PUBLIC SERVANTS’ COMMUNICATIVE COMPETENCE
Keywords: компетентність; комунікативна компетентність; комунікативні навички; комунікативні бар’єри; комунікативні якості; комунікативні вміння; competence; communicative competence; communication skills; communication barriers; communication qualities; communication abilities; 159.9:06.053.52